Maintenance processes in Huanuco Quechua and the alternation of the direct evidential suffix {-mi}. An approach from Formal Semantics - Flores Chavez, Maybe (2021)
In Huanuco Quechua, there is an alternation in the use of the direct evidential {-mi} within sentences describing maintenance processes. The main objective of this work is to describe such evidentiality in processes of internal and external experience, as well as in others that refer to a notion of control that transmits certainty about the veracity of the statement in an alternate way. As explained by Floyd (1997), in the semantic network of such particle are grouped uses that at first glance may seem incompatible, but are related. For the analysis, formalizations of formal semantics are used (Montague, 1970), which give an account of the syntactic structures involved in the states and the processes derived from them. It is concluded that the use of the suffix '-mi' has an alternation motivated by semantic factors oriented to the experience gradually.